A fuzzy MCDM approach for choosing a tourism destination in Portugal - Genç, T.; Filipe, J. A. (International Journal of Business and Systems Research, 2016)
In this paper, it is intended to create a methodology in order to have a multi criteria approach for choosing a tourist destination region or place. Involving a gridline scheme for selection a tourism destination, several criteria will be defined in order to create the basis for the utilisation of the model for electing a destination. The first step involves the description of the features of the possible destinations like Lisbon, Alentejo, Algarve and Alto Douro Region and in which the methodology may be applied. Tourism destination selection is a multi criteria decision making (MCDM) problem including both multi alternatives and criteria and has a great importance for many travellers. To do so, we use the fuzzy technique for order performance by similarity to ideal solution (TOPSIS), an MCDM method based on fuzzy sets in deciding about a tourism destination. Generally, it is difficult to model the real life problems with crisp data. For that reason, we take advantage of using linguistic variables to select the best tourist destination in Portugal.